Contemplating Music: Challenges to Musicology - Kerman, Joseph (Cambridge, MA Harvard University Press, 1986)
Contemplating Music is a book for all serious music lovers. Here is the first full-scale of ideas and ideologies in music over the past forty years; a period during which virtually every aspect of music was transformed. With this book, Joesph Kerman establishes the place of music study firmly in the mainstream of modern intellectual history. He treats not only the study of the history of Western art music--with which musicology is tradtionally equated--but also sometimes vexed relations between music history and other fields: music theory and analysis, ethnomusicology, and music criticism.Kerman sees and applauds a change in the study of music toward a critical orientation, As examples, he presents a fascinating vignettes of Bach research in the 1950's and Beethoven studies in the 1960's. He sketched the work of prominent scholars and theorists: Thurston Dart, Charles Rosen, Leonard B. Meyer, Heinrich Schenker, Miltion Babbit, and many others. And he comments on such various subjects as the amazing absorption of Stephen Foster's songs into the cannons of "black" music, the new intensity of Verdi research, controversies about performance on historical instruments, and the merits and demerits of The New Grove Dictionary of Music and Musicians.
Keywords: Music philosophy and esthetics; Historically informed performance